Recurrence factors in pediatric ameloblastoma: Clinical features and a new classification system. Issue 10 (19th July 2019) - Yang, Rong; Tang, Yu; Zhang, Xu; Liu, Zheqi; Gokavarapu, Sandhya; Lin, Chengzhong; Ren, Zhenhu; Zhou, Yongmei; Cao, Wei; Ji, Tong
Abstract: Background: Ameloblastomas of jaw in the pediatric population are a rare clinical entity and have not been well addressed in the literatures. The present retrospective study analyzed the risk factors associated with recurrence of pediatric ameloblastomas. Methods: Cases of primary pediatric ameloblastomas seen in a tertiary hospital between 2005 and 2015 were analyzed to identify the clinical factors associated with recurrence. Results: There were a total of 104 cases of primary pediatric ameloblastomas. The overall mean maximum tumor diameter was 4.11 ± 1.339 cm. The receiver operating characteristic curve and the Youden Index showed an optimal cutoff point of 4.95 cm to accurately predict recurrence. Bone cortex/soft tissue invasion were associated with tumor recurrence ( P < .001). Conclusions: The maximum tumor diameter, root resorption, and bone cortex/soft tissue invasion were risk factors for recurrence of pediatric ameloblastomas. The new classification system may serve as a predictor of recurrence in pediatric ameloblastomas.